Penerapan Model Mengajar Menginduksi Perubahan Konsep (M3PK) Simson Tarigan Dan Cooperative Learning Tipe STAD Dengan Menggunakan Multimedia Berbasis Komputer Dalam Meningkatkan Sikap Toleransi Dan Hasil Belajar Larutan Penyangga Pada Siswa Kelas XI MAN - Badlisyah, Teuku (UIN AR-RANIRY, 2014)
This study aims to determine: (1) The effect of the application of M3PK and Cooperative Learning STAD to tolerance towards students and student learning outcomes. (2) Effect of computer-based multimedia and media tolerance of real objects on students and student learning outcomes. (3) The interaction between M3PK and Cooperative Learning STAD with computer-based multimedia and real objects media to tolerance towards students and student learning outcomes. (4) The most optimal learning model to improve the tolerance of students and student learning outcomes. The population in this study were all students of Madrasah Aliyah is in Banda Aceh second semester of academic year 2012/2013, and the sample was 115 people came from two classes of experiments in Madrasah Aliyah Negeri 1 Banda Aceh, and two classes of experiments in Madrasah Aliyah Negeri 3 Banda Aceh. 1 experimental class taught by Teaching Model Induces Changes in Concept (M3PK) multimedia-based computer. 1 experimental class taught by Teaching Model Induces Changes in Concept (M3PK) using media real thing. 3 experimental class taught by cooperative learning STAD type of multimedia-based computer. 4 experimental class taught by cooperative learning STAD type using media real thing. The research data were collected from a sample of students' tolerance is data obtained from observation and student learning outcome data were obtained from the achievement test in the form of multiple choice. Has made the data requirements in the form of normality and homogeneity test, which showed that normal data and homogeneous. The hypothesis was tested by Two Way ANOVA at the significant level of 0.05 using SPSS program for Windows 19 version. Based on the data analysis and hypothesis testing are carried out found that: (1) There is a significant effect of learning strategies to students' tolerance. (2) There is a significant effect of learning strategies on learning outcomes of students. (3) There is no significant effect of multimedia learning tolerance attitude towards students. (4) There is no significant effect of multimedia learning on student learning outcomes. (5) There is interaction between learning strategy and learning multimedia tolerance attitude towards students. (6) There is interaction between learning strategy with multimedia learning on student learning outcomes. (7) The model of learning that the most optimal in improving tolerance M3PK students are learning model that integrates with media use real objects in the learning process. (8) The model lesson that the most optimal in improving student learning outcomes is M3PK learning model that integrates with media use real objects in the learning process.